Peculiar emission from the new VHE gamma-ray source H1722+119. Issue Volume 12:Issue S324(2016) (23rd June 2017) - Terzić, T.; Stamerra, A.; D'Ammando, F.; Raiteri, C. M.; Villata, M.; Verrecchia, F.; Kurtanidze, O.
Abstract : The BL Lac object H1722+119 was observed in the very high energy band (VHE, E > 100 GeV) by the MAGIC (Major Atmospheric Gamma-ray Imaging Cherenkov) telescopes (Aleksić et al. 2016a, b)) between 2013 May 17 and 22, following a state of high activity in the optical band measured by the KVA (Kungliga Vetenskapsakademien) telescope. Optical high states are often used to trigger MAGIC observations, which result in the VHE γ-ray signal detection (see e.g. Aleksić et al. 2015, Ahnen et al. 2016 and references therein).